Standard‐ or high‐dose oxytocin for nulliparous women with confirmed delay in labour: quantitative and qualitative results from a pilot randomised controlled trial. Issue 11 (21st June 2013) - Kenyon, S; Armstrong, N; Johnston, T; Walkinshaw, S; Petrou, S; Howman, A; Cheed, V; Markham, C; McNicol, S; Willars, J; Waugh, J; ,
<x xml:space="preserve">Abstract</x> Objective Evidence suggests that a high dose of oxytocin for nulliparous women at 37–42 weeks of gestation with confirmed delay in labour increases spontaneous vaginal birth. We undertook a pilot study to test the feasibility of this treatment. Design Pilot double‐blind randomised controlled trial. Setting Three teaching hospitals in the UK. Population A total of 94 consenting nulliparous women at term with confirmed delay in labour were recruited, and 18 were interviewed. Methods Women were assigned to either a standard (2 mU/min, increasing every 30 minutes to 32 mU/minute) or a high‐dose regimen (4 mU/minute, increasing every 30 minutes to 64 mU/minutes) oxytocin by computer‐generated randomisation. Simple descriptive statistics were used, as the sample size was insufficient to evaluate clinical outcomes. The constant comparative method was used to analyse the interviews. Main outcomes measures The main outcome measures: number of women eligible; maternal and neonatal birth; safety; maternal psychological outcomes and experiences; health‐related quality of life outcomes using validated tools and data on health service resource use; incidence of suspected delay of labour (cervical dilatation of <2 cm after 4 hours, once labour is established); and incidence of confirmed delay of labour (progress of <1 cm on repeat vaginal examination after a period of 2 hours). Results We successfully developed systems to recruit eligible women in labour and to collect data. Rates of spontaneous vaginal birth (10/47 versus 12/47, RR 1.2, 95% CI 0.6–2.5) and caesarean section (15/47 versus 17/47, RR 1.1, 95% CI 0.6–2.0) were increased, and rates of instrumental birth were reduced (21/47 versus 17/47, RR 0.8, 95% CI 0.5–1.3). No evidence of increased harm for either mother or baby was found. The incidences of suspected delay (14%) and confirmed delay (11%) in labour were less than anticipated. Of those who did not go on to have delayed labour confirmed, all except one woman gave birth vaginally. Conclusions A pilot trial assessing the efficacy of high‐dose oxytocin was feasible, but uncertainty remains, highlighting the need for a large definitive trial. The implementation of national guidance of suspected and confirmed delay in labour is likely to reduce intervention.